Discharge of deeply rooted fluids from submarine mud volcanism in the Taiwan accretionary prism - Chen, Nai-Chen (Sci Rep, 2020)
Qualitative and quantitative assessments of fluid cycling are essential to address the role and transport of deeply sourced fluids in subduction systems. In this study, sediment cores distributed across a submarine mud volcano (SMV) offshore southwestern Taiwan were investigated to determine the characteristics of fluids generated through the convergence between the Eurasian and Phillippine Sea Plates. The low dissolved chloride concentration combined with the enrichment of (18)O, and depletion of (2)H of pore fluids suggest the discharge of deep freshwater formed by smectite dehydration at an equilibrium temperature of 100 to 150 °C. The upward fluid velocities, decreasing from 2.0 to 5.0 cm yr(−1) at the center to a negligible value at margin sites, varied with the rate and efficiency of anaerobic methanotrophy, demonstrating the impact of fluid migration on biogeochemical processes and carbon cycling. By extrapolating the velocity pattern, the flux of fluids exported from 13 SMVs into seawater amounted up to 1.3–2.5 × 10(7) kg yr(−1), a quantity accounting for 1.1–28.6% of the smectite-bound water originally stored in the incoming sediments. Our results imply that SMVs could act as a conduit to channel the fluids produced from great depth/temperature into seafloor environments in a subduction system of the western Pacific Ocean.